SUSTAINABILITY COST ACCOUNTING - PART 1: A MONETARY PROCEDURE TO EVALUATE THE SUSTAINABILITY OF TECHNOLOGIES IN THE SOUTH AFRICAN PROCESS INDUSTRY - Brent, A. C.; Van Erck, R.P.G.; Labuschagne, C. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The development and management of new technologies is fundamental to the manufacturing sector as a core operational initiative. Managers of a new technology are increasingly pressurised to consider the economic, environmental, and social impacts associated with the life cycle of the technology (and product) during decision-making